ENHANCING EVIDENTIARY FAIRNESS IN INDONESIAN CRIMINAL LAW: ADAPTING BRADY V. MARYLAND PRINCIPLES FOR EQUITABLE TRIALS - Dharma Setiawan Negara; Erwin Susilo (Kanun Jurnal Ilmu Hukum, 2025)
This article examines the imbalance in the evidentiary system in criminal cases in Indonesia, especially regarding the limited authority of the public prosecutor in assisting the defendant to present mitigating evidence. This problem is contrary to the principle of equality of arms which requires equality between the public prosecutor and the defendant in evidence. By adopting principles from Brady v. Maryland, this article provides a normative framework to enhance the Indonesian criminal evidence system, particularly by advocating for clearer prosecutorial disclosure obligations. While Brady originates from the common law tradition, its core principle ensuring fairness through evidence disclosure can be adapted within Indonesias civil law system through judicial interpretation and procedural reforms, aligning with the broader aim of strengthening due process and evidentiary fairness. A normative juridical approach is used by analyzing primary and secondary legal materials, including a comparative study of the application of the Brady Rule in the United States of America. The results show that the need to reform Indonesian criminal procedural law by regulating the obligation of public prosecutors to actively reveal evidence that exculpates defendants in order to ensure substantive equality. This proposed norm to create criminal trials that are quitable in achieving material truth, ensuring only guilty parties are sentenced, while the innocent are acquitted.